Tekst op voorzijde: 'De eerste foto van het Prinseljk Gezin na de geboorte van Prinses Margriet ...' (1943)
Tekst op voorzijde: 'De eerste foto van het Prinseljk Gezin na de geboorte van Prinses Margriet ...'.